Non-Parametric Test for Ordered Medians: The Jonckheere Terpstra Test - Ali, Arif; Rasheed, Abdur; Siddiqui, Afaq Ahmed; Naseer, Maliha; Wasim, Saba; Akhtar, Waseem (International Journal of Statistics in Medical Research, 2015)
In clinical trials, sample size is usually lesser as compared to other epidemiological studies to make it more feasible and cost effective. Small sizes of such trials discourage the use of parametric test due to violation of the assumption under which they are applicable. Therefore, the use of nonparametric test is substantial in clinical trials to test two or more independent samples. The Kruskal-Wallis h test is an alternative to one-way ANOVA and can be used to identify significant differences among different populations. When we have several independent samples and assumed to be arranged orderly, Jonckheere Terpstra test is a best choice to compare population medians instead of means. For the application of Jonckheere Terpstra test the data from the study of cleaning methods for ultrasound probes are used. The Jonckheere Terpstra test is recommended over Kruskal-Wallis h test as it compares and provides significant difference between more than two population medians when they arranged in order. Therefore, the aim of this research paper was to explore the use and significance of Jonckheere-Terpstra test with the use of practical example.